(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the multifaceted concept of professional competencies among gymnastics coaches. The analysis indicates that well-developed professional competencies are crucial for ensuring a coach’s employability and competitiveness within the field. To identify the structural components of these competencies, key professional requirements were substantiated. The study establishes that the professional competencies of gymnastics coaches encompass six core domains: theoretical and methodological knowledge, practical expertise, psychological and pedagogical competence, organizational and managerial skills, diagnostic and analytical abilities, and research competence. The study revealed that theoretical and methodological competence is essential for enhancing the effectiveness of the educational and training process. This competence entails the development of theoretical knowledge, an understanding of didactic principles, and the ability to apply contemporary training methods in the practical activities of gymnastics coaches. Practical competence encompasses technical proficiency, methodological adaptability, and the capacity to ensure gymnast safety, thereby facilitating the efficient execution of educational and training processes. Notably, this component enables coaches to foster the physical fitness and technical skills of athletes while supporting their confidence and motivation to achieve success in gymnastics. Psychological and pedagogical competence represents a multifaceted component of a coach’s professional skills, comprising the ability to motivate athletes, establish a supportive psychological environment, and apply modern pedagogical and psychological strategies in training. Organizational and managerial competence involves planning training sessions tailored to athletes’ individual characteristics, maintaining effective communication with stakeholders in the sports environment, and managing a sports group. Diagnostic and analytical competence requires the ability to objectively assess athletes’ performance, utilize modern monitoring and functional diagnostic technologies, and conduct self-reflection on professional practice. Lastly, research competence entails familiarity with contemporary methods, the application of modern technologies, and their adaptation to the individual needs of athletes. It has been established that the structural components of a gymnastics coach’s professional competence constitute a comprehensive foundation for facilitating the harmonious development of athletes and achieving high-performance outcomes in sports.